CYCLIC BEHAVIOUR OF LIGHTLY REINFORCED CONCRETE COLUMNS WITH NON-DUCTILE LAP SPLICES - Rizki Amalia Tri Cahyani; Ari Wibowo; Wisnumurti Wisnumurti (Media Teknik Sipil, 2018)
Experimental testing of lightly reinforced concrete column was conducted to investigate the collapse behavior of such column under cyclic lateral loading. Six column specimens, which have low longitudinal reinforcement and lack of confinement, were detailed with no lap splice, and non-ductile lap splice within or outside critical region. Placing the short, unconfined column's lap splice within critical region caused peak moment to fall short under its nominal moment capacity. In contrast, moment capacity of the specimen containing non-ductile lap splice outside critical region was in close agreement with those of specimen without lap splice. However, its inelastic damage region was moving away from the beam-column interface, resulted in degradation of drift capacity and rapid degradation of lateral strength. The presence of non-ductile lap splice outside critical region also potentially shift column's collapse mechanism from flexure to flexure-shear critical. The ability of lightly reinforced concrete columns to maintain its axial load carrying capacity to large drift ratios despite heavy damage and significant loss of lateral load carrying capacity indicates that lap splice failure does not create sudden collapse hazard.